ART ACTIVITIES AS A MEDIUM FOR CRITICAL THINKING IN THE "LET'S SHARE THE ART" PROGRAM - Ahmad Naufalul Umam (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2022)
Political provocation on governor election in Jakarta had its spill-over effect on youths' increased prejudice in a national scale. With this concern, stakeholders initiated an intervention program named "Let's Share the Art" for high school students to facilitate discussions that promote cognitive flexibilities. The program was held once per week in 7 meetings. It was expected that the program will lower the need for closure (NFC) and raise the critical thinking mindset (CTM) scores of the beneficiaries. Two high schools that partnered with the program initiator were selected, with a total of 82 students participated in the research. Contrary to the hypotheses, we found no significant change in both measurements from both schools. However, separated analysis showed that there are some indications of changes regarding to certain situational and contextual matters. Notwithstanding the fact that the result could not be generalized on Indonesian youth, but the subtle impact of art activities on cognitive flexibility for teenagers was discussed, with the additional notes on how to implement such program in the future.